(untitled) - Kawahito, Kiyoshi (New York, 1972)
This book introduce reconstruction and development. The Japanese steel industry today. U. S. steel imports from Japan.
Keywords: Thương mại và công nghiệp thép,Steel industry and trade; Nhật Bản,Japan